Relationship between technological self-efficacy and english learning efficiency among non-english major students in Jiangxi, China - Men, Zhang; Siew Ping, Wong (Journal of Islamic, Social, Economics and Development, 2025)
This study examines the relationship between technological self-efficacy and English learning efficiency among non-English major university students in Jiangxi, China. As mobile learning applications and digital tools become increasingly integrated into educational settings, understanding the relationship between technological self-efficacy and English language learning efficacy is crucial, especially for students who do not major in English language. A quantitative research design was employed, using a cross-sectional survey method to collect data from a sample of 384 students selected through stratified random sampling. The survey assessed students' levels of technological self-efficacy and their English learning efficiency, utilizing a structured questionnaire with Likert scale items. The data were analyzed using descriptive statistics and Pearson correlation analysis to explore the relationship between the variables. The results revealed a strong positive correlation between technological self-efficacy and English learning efficiency, indicating that students who are more confident in using technology tend to achieve higher efficiency in learning English. This finding underscores the importance of enhancing technological self-efficacy to improve English language outcomes for non-English major students. The study contributes valuable insights into how digital skills are related to language acquisition, suggesting that integrating technology effectively in educational practices can enhance learning efficiency. These findings have implications for educators and policymakers in designing strategies that leverage technology to support language learning, particularly in non-English major contexts, thereby improving students' proficiency and success in acquiring English as a second language.